Highly conductive pitch-based carbon nanofiber/MnO2 composites for high-capacitance supercapacitors - Yang, Cheol-Min; Kim, Bo-Hye (ELSEVIER SCIENCE SA, 2018)
PAN/pitch-based carbon nanofiber/MnO2 (PPMn-CNF) composites are fabricated by electrospinning to obtain a new type of electrode material for application in high-capacitance electrical double-layer capacitors (EDLCs). The energy storage capabilities of these PPMn-CNFs reveal a maximum specific capacitance of 188 Fg(-1) and a maximum energy density of 20.5-15.8 Whkg(-1) in the power density range of 400-10,000 Wkg(-1). Furthermore, the PPMn-CNF electrode shows good rate capability without a significant decrease at high rate. The high electrical conductivity of the pitch promotes the accessibility into the micropores and the adsorption efficiency onto the electrode surface of electrolyte ions. Therefore, the high electrical conductivity and large surface area of the PPMn-CNF composites are beneficial for the storage of charge carriers and induce a short course for charge transport, which maximizes the specific capacitance and ensures good capacitive capability. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: MNO2 NANOPARTICLES; PERFORMANCE; GRAPHENE; FIBER; NITROGEN; OXIDE